DIABETES MELLITUS AND ANTIDIABETICS WITH REFERENCE TO ALPHA GLUCOSIDASE INHIBITORS - 2Aparoop Das1Partha Sarathi Bairy*, 1Brajesh Shankar (Journal of Biomedical and Pharmaceutical Research, 2017)
Diabetes mellitus is a long term disorder with high blood glucose level associated with other complications. Every year it takes many people in its list to affect. With modern lifestyle and food behavior incidence of diabetes increasing day by day. Proper lifestyle, exercise and proper diet is the mainstay to manage this condition though many drugs are available in the market. Insulin is the first choice of chemical for treatment as insulin control the circulatory blood glucose and its entry to other cells for energy. Other oral antidiabetics like biguanides, sulfonylureas, thiazolidinediones, alpha-glucosidase inhibitors, meglitinides etc are available in the the market for monotherapy as well as combination therapy but they are neither efficient like insulin nor free from adverse effects. The aim of this review is to present in brief about the diabetes burden worldwide with its pathophysiology, diagnosis and proper management. Alpha-glucosidase inhibitors are discussed here as they proved to control the postprandial blood glucose level significantly and some other new targets for glycemic control. Keywords: diabetes mellitus, glucose, insulin, alpha-glucosidase, obesity, exercise.